Selection of the silicon sensor thickness for the Phase-2 upgrade of the CMS Outer Tracker. (22nd November 2021) - Adam, W.; Bergauer, T.; Blöch, D.; Dragicevic, M.; Frühwirth, R.; Hinger, V.; Steininger, H.; Beaumont, W.; Di Croce, D.; Janssen, X.; Kello, T.; Lelek, A.; et al.
Abstract: During the operation of the CMS experiment at the High-Luminosity LHC the silicon sensors of the Phase-2 Outer Tracker will be exposed to radiation levels that could potentially deteriorate their performance. Previous studies had determined that planar float zone silicon with n-doped strips on a p-doped substrate was preferred over p-doped strips on an n-doped substrate. The last step in evaluating the optimal design for the mass production of about 200 m 2 of silicon sensors was to compare sensors of baseline thickness (about 300 μm) to thinned sensors (about 240 μm), which promised several benefits at high radiation levels because of the higher electric fields at the same bias voltage. This study provides a direct comparison of these two thicknesses in terms of sensor characteristics as well as charge collection and hit efficiency for fluences up to 1.5 × 10 15 neq /cm 2 . The measurement results demonstrate that sensors with about 300 μm thickness will ensure excellent tracking performance even at the highest considered fluence levels expected for the Phase-2 Outer Tracker.